Clinical features and complications of liver cirrhosis in a high-altitude population (Huancayo, 3,250 m a.s.l.) - Calderón Gerstein, Walter (2020)
Objective: Liver cirrhosis is responsible for significant morbidity and mortality. This research aims to determine the clinical presentation, etiology and complications of patients with liver cirrhosis from a population living at a high altitude region in Peru. Materials and methods: A retrospective study of the clinical presentation and complications of liver cirrhosis was conducted. One hundred eight (108) medical records of patients with liver cirrhosis admitted to the Internal Medicine Service of the Hospital Nacional Ramiro Prialé Prialé, Huancayo,were evaluated between 2010 and 2012. Results: Patients’ mean age was 60.5 years (range: 12–82 years) and 62.9 % were males. The most common etiology was alcohol consumption (63 %), followed by chronic hepatitis B and C (7.4 % and 2.8 %, respectively). Fifty-eight point three percent (58.3 %) of the patients had a Child-Pugh class B score and 31.30 % of them had a Child-Pugh class C score. The most frequent clinical presentation was abdominal distension (87 %). The most common complications were ascites (56 %), hepatic encephalopathy (47.2 %) and hepatorenal syndrome (8.3 %). Conclusions: Alcoholic liver cirrhosis was the most common etiology. The most frequent complications were ascites and hepatic encephalopathy.